Gelation and structural characteristics of deacetylated salep glucomannan - Kurt, Abdullah; Kahyaoglu, Talip (ELSEVIER SCI LTD, 2017)
Controlled deacetylation of salep glucomannan (SGM) was performed in this study for the first time. SGM, with different degrees of deacetylation (DD), were prepared with the control sample. The rheological properties of SGM were affected by the deacetylation process. Deacetylated samples showed lower apparent viscosities and pseudoplastic characteristics. The gelation of SGM occurred at 90 and 100% DD for 0.75% and 1% SGM concentrations, and increasing the concentration from 0.5% to 1% increased the gelation kinetics of the samples. The whiteness index and strength of salep gel increased as the DD and concentration increased. The remarkable decrease in absorption bands at approximately 1736 cm(-1) with deacetylation was detected with an FTIR experiment. The SEM images showed that deacetylation resulted in a smooth surface. Removing acetyl groups with the aid of alkali weakened the solubility but improved the thermal stability of SGM, which was determined with DSC and TGA experiments. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Salep; Glucomannan; Deacetylation; Rheology; Gelation; KONJAC GLUCOMANNAN; RHEOLOGICAL PROPERTIES; PHYSICOCHEMICAL CHARACTERIZATION; MECHANOCHEMICAL TREATMENT; FUNCTIONAL-PROPERTIES; AQUEOUS-SOLUTION; GELS; GUM; BEHAVIOR; POLYSACCHARIDES; Chemistry; Food Science & Technology